2019
DOI: 10.26576/profesi.321
|View full text |Cite
|
Sign up to set email alerts
|

Manfaat Massage Tengkuk Dengan Minyak Zaitun Untuk Mengurangi Nyeri Kepala Pasien Hipertensi

Abstract: Hipertensi atau tekanan darah tinggi adalah suatu peningkatan tekanan darah di dalam arteri. Prevalensi hipertensi di Indonesia sebesar 26,5 persen dari total penduduk di Indonesia. Studi pendahuluan di dapatkan sebanyak 18 orang yang mengalami hipertensi dengan nyeri kepala. Tujuan penelitian ini untuk mengetahui manfaat terapi massage tengkuk dengan minyak zaitun untuk mengurangi nyeri pada pasien hipertensi. Penelitian ini merupakan penelitian kuantitatif dengan desain Quasi Eksperimental design rancangan O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Such as lavender aromatherapy in lowering blood pressure, health care should prepare some drops of aromatherapy and diffuser (Maisi, Suryono, Widyawati, Suwondo, & Kusworowulan, 2017); or they need a banana when using ambon banana as the alternative way in reducing blood pressure (Susanti, & Resti, 2019) Moreover, any drugs, surgery, and special medic equipment are not required to give hypnosis; only use the power of suggestion, which will relax the patients directly and make them comfortable quickly (Iserson, 2014;Larasati & Wibowo, 2012). Yoganita, Sarifah, & Widyastuti (2019) suggested that nape massage and hypnosis can reduce blood pressure, either systolic (15.62 mmHg) or diastolic (6.72 mmHg). Hypnotherapy can also overcome stress, relax the body, inhibit cortisol hormone secretion, and this condition prevents vasoconstriction of blood vessels so that blood pressure decreases (Purnomo, Nur, Rahim, & Pulungan, 2020) In terms of fetal heart rate (FHR), relaxation reduced the basal fetal heart rate (Akbarzade, Rafiee, Asadi, & Zare, 2015).…”
Section: Nursing Practicesmentioning
confidence: 99%
“…Such as lavender aromatherapy in lowering blood pressure, health care should prepare some drops of aromatherapy and diffuser (Maisi, Suryono, Widyawati, Suwondo, & Kusworowulan, 2017); or they need a banana when using ambon banana as the alternative way in reducing blood pressure (Susanti, & Resti, 2019) Moreover, any drugs, surgery, and special medic equipment are not required to give hypnosis; only use the power of suggestion, which will relax the patients directly and make them comfortable quickly (Iserson, 2014;Larasati & Wibowo, 2012). Yoganita, Sarifah, & Widyastuti (2019) suggested that nape massage and hypnosis can reduce blood pressure, either systolic (15.62 mmHg) or diastolic (6.72 mmHg). Hypnotherapy can also overcome stress, relax the body, inhibit cortisol hormone secretion, and this condition prevents vasoconstriction of blood vessels so that blood pressure decreases (Purnomo, Nur, Rahim, & Pulungan, 2020) In terms of fetal heart rate (FHR), relaxation reduced the basal fetal heart rate (Akbarzade, Rafiee, Asadi, & Zare, 2015).…”
Section: Nursing Practicesmentioning
confidence: 99%